The Right to Inclusive Education for Children with Disabilities through the Perspective of Law - Dzakyyah Evelia Dian Safitri; Yulianto (Journal of Interdisciplinary Social Sciences and Humanities, 2025)
Children with disabilities have the same rights to obtain proper education as regulated in various national regulations and international conventions. However, in reality, many children with disabilities still face various obstacles in accessing education, both in terms of physical, social, economic, and policy. This article aims to examine children with disabilities in obtaining their rights to proper education, by highlighting the various challenges faced and the various efforts that have been and can be made by the government, schools, and the community. The research method used is descriptive qualitative research with a literature study approach. The results of the study indicate that limited school infrastructure, lack of parental understanding of inclusive education, and social stigma are the main obstacles. On the other hand, cross-sector collaboration and increasing public awareness are the keys to strengthening a disability-friendly education system. This study emphasizes the importance of a shared commitment to ensuring that every child, without exception, can enjoy their right to education equally and with dignity.